2021
DOI: 10.3389/fpsyg.2021.708536
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropsychological Profile of Severe and Enduring Anorexia Nervosa: A Systematic Review

Abstract: Characteristics of Severe and Enduring Anorexia Nervosa (SE-AN) are being investigated to differentiate the patients experiencing SE-AN from those at earlier stages of the AN disease. The current systematic review was the first step in exploring neuropsychological functioning as a potentially identifying characteristic for long-term presentations. With a subgroup of AN patients reflecting a unique neuropsychological profile that is proportionate to the quantity of patients that go on to develop SE-AN, it was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 116 publications
(212 reference statements)
0
10
0
Order By: Relevance
“…Our moderator analyses also showed a significant effect of age, revealing that older participants exhibited a stronger negative effect, that is, poorer neuropsychological test performance. Previous studies have suggested that prolonged illness may amplify neuropsychological difficulties (Lang, Stahl, et al., 2014) with preliminary evidence from a recently conducted systematic review suggesting this may be particularly relevant in the domains of decision‐making, intellectual functioning and set shifting abilities (Broomfield, Stedal, & Touyz, 2021). Harper, Brodrick, Van Enkevort, and McAdams (2017) proposed that neuropsychological functioning is an important predictor of patients’ ability to recover.…”
Section: Discussionmentioning
confidence: 99%
“…Our moderator analyses also showed a significant effect of age, revealing that older participants exhibited a stronger negative effect, that is, poorer neuropsychological test performance. Previous studies have suggested that prolonged illness may amplify neuropsychological difficulties (Lang, Stahl, et al., 2014) with preliminary evidence from a recently conducted systematic review suggesting this may be particularly relevant in the domains of decision‐making, intellectual functioning and set shifting abilities (Broomfield, Stedal, & Touyz, 2021). Harper, Brodrick, Van Enkevort, and McAdams (2017) proposed that neuropsychological functioning is an important predictor of patients’ ability to recover.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with AN present with varying degrees of underweight and starvation and different disease durations. In general, both somatic and mental problems increase with the degree and duration of underweight/starvation (Broomfield et al., 2021; Gibson et al., 2020). If leptin plays an important role in the development of the clinical symptoms of AN, the variability among patients with respect to FYI (leptin level, sObR), BMI, fat mass, disease duration and the degree of the adaptation to starvation warrants consideration.…”
Section: Methodsmentioning
confidence: 99%
“…Malnutrition has been shown to affect the brain in a variety of ways including causing increased obsession with food, depression, apathy, and impulsivity, all of which can reinforce AN cognitions and cloud decisionmaking [18][19][20]. And, ambivalence regarding treatment is common, which may adversely impact an individual's decision-making regarding necessary treatment for their AN [21][22][23][24].…”
Section: Emergency Psychiatric Issuesmentioning
confidence: 99%